TRANSFORMATIONAL LEADERSHIP MANAGEMENT IN IMPROVING THE PERFORMANCE QUALITY OF EDUCATIONAL STAFF AT THE STATE HIGH SCHOOL (MAN) IN TARAKAN - Asmawan (Journal of Education and Teaching Learning, 2026)
This qualitative case study explores the implementation of transformational management by the Madrasah Principal at MAN Tarakan City and its impact on employee performance. Data were collected through observation, documentation, and interviews, then analyzed using data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques. The results indicate that transformational leadership is implemented through four main pillars: strong role modeling, inspirational motivation, intellectual stimulation for innovation, and individual attention. This approach has been proven to significantly improve employee performance, as reflected in discipline, professional independence, intrinsic motivation, and a sense of ownership of the institution's vision. The implication is that the integration of transformational leadership with religious values ​​successfully builds an adaptive and productive organizational culture. This success confirms that improving educational quality relies heavily on the psychological and emotional empowerment of staff by leadership. Practically, this study recommends the importance of transformational leadership training to maintain sustainable performance within the State Madrasah Aliyah (Islamic Senior High School).